Political Opinions Appearing in Phleng - Rua (Boat Song) at Ampore Khuan-niang in Songkhla Province - ไวทยะวณิช, กุณฑลีย์ (Journal of the Faculty of Arts, Silpakorn University, 2019)
This study Amhoe aimed to examine the political opinions that appear in Phleng - Rua (Boat Song) at Amphoe Khuan-niang in Songkhla Province. Qualitative research was used to analyze the content of 12 songs along with participatory and non-participatory observations. The studied results wer presented using descriptive analysis. It was found that Phleng - Rua at Amphoe Khuan-niang in Songkhla Province showed political opinions as follows. 1) Political opinions towards elections such as exercising their right in electing senators, rejecting vote buying, and understanding the process of election. 2) Political opinions towards administration such as about being a good leader and administration policies. 3) Opinions on current situations such as political conflicts between Yellow Shirts, and Red Shirts, and 3-southern border provinces' political situations.